Comparison of High Boost Ratio Hybrid Transformer DC-DC Converter with Multistage Converter - Soedibyo, Soedibyo; Anam, Sjamsjul (JAVA Journal of Electrical and Electronics Engineering, 2015)
Energy of Photovoltaic is one of energy resource that potential to be developed in Indonesia. Output power of Photovoltaic is changing according to changes of sunirradiance. Energy sources that produce DC low voltage require a step-up converter to increase the voltage before it is converted into AC voltage.To optimize the system, step-up converters must have a high voltage ratio and high efficiency at all of loading level and wide voltage input range. In this research will be compared betweem multistage converter and high voltage ratio boost converter that utilizes combination of pulsewidth modulation (PWM) operating mode and a resonant mode.This converter only requires one switch, so it’s easier in the controlling. This researh results showed with same duty cycle and voltage input, transformer hybrid method can produce power output greater than multistage. The voltage output of hybrid transformer can also achieve steady state faster than using a hybrid converter.So the hybrid converter transformer has the better ability than multistage converter and can be implemented in alternative energy resources that produce a low DC voltage such as photovoltaics.